The Analisis Problematika Jual Beli Online di Era Digital dalam Perspektif Fiqih Muamalah - Rika Rahmawati; Riva Aprilia; Pebi Pebrianti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study describes the problems of online buying and selling in the digital era from the perspective of fiqh muamalah. The background of this research is the rapid development of digital technology, which has encouraged changes in people's transaction patterns from conventional systems to online-based transactions. Online buying and selling have become one of the most popular forms of modern trade because it offers convenience, time efficiency, and wide market reach. However, behind these conveniences, various problems arise, such as unclear product information, manipulation of information, fraud, delivery delays, and discrepancies between the goods received and the descriptions offered. These problems raise questions regarding the suitability of online buying and selling practices with the principles of fiqh muamalah in Islam. This study uses a descriptive qualitative method with a library research approach. Data collection techniques were carried out through the study of various literature sources, such as books, scientific journals, articles, and other sources related to online buying and selling and fiqh muamalah. The results of the study indicate that online buying and selling practices are basically permissible in Islam as long as they fulfill the pillars and conditions of sale and purchase, such as clarity of the contract, mutual consent between both parties, clarity of the transaction object, and avoidance of elements of gharar, tadlis, usury, and fraud. In addition, Islamic business ethics values such as honesty, trustworthiness, responsibility, and justice are important principles in maintaining security and trust in digital transactions. Nevertheless, online buying and selling practices still face various obstacles, including the low awareness of some business actors regarding Islamic business ethics and the lack of public understanding of sharia transactions. Overall, the application of fiqh muamalah principles in online buying and selling is very important to create electronic transactions that are fair, safe, and in accordance with Islamic values.